Peripheral Retinal Ischemia and Secondary Neovascular Glaucoma after Cerclage for Retinal Detachment: A Case Report - Feliciana Menna; Marcel Menke; Markus Tschopp (Case Reports in Ophthalmology)
Introduction: Various surgical techniques, including 360° buckling surgery with a retinal cerclage, have been employed to achieve retinal reattachment. Although retinal cerclage is generally effective, long-term complications can arise. Peripheral retinal ischemia and secondary neovascular glaucoma are rare, but serious complications can occur even years after successful retinal reattachment. Case Presentation: We report a rare case of a 79-year-old woman who underwent 360° buckling surgery with cerclage for retinal detachment 10 years ago. Although the initial surgery successfully reattached the retina, she later developed a complication characterized by peripheral retinal ischemia and secondary neovascular glaucoma. Conclusion: Early detection and prompt management of such complications are crucial to prevent irreversible visual impairment.